Analysis Of The Roles & Interactions Of Political Actors In Improving The Quality Of Public Service In Puskesmas: (Study At Puskesmas Karang Rejo, West Tarakan Subdistrict, Tarakan City North Kalimantan Province, Indonesia) - Tri Lestari Hadiati; Sugianti Sugianti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Puskesmas are the spearhead of the government in providing basic health services to the community in Indonesia. Puskesmas are required to provide excellent quality services to the community, but these expectations have not been met. Government efforts are then made through independent financial management of the Regional Public Service Agency (BLUD). Karang Rejo Health Centre is one of the Health Centres that successfully received a designation by the Government of Tarakan City, North Kalimantan Province as one of the Independent Health Centres with BLUD management. This study aims to analyse the role & interaction between political actors or leaders in Puskesmas in improving the quality of excellent service at Karang Rejo Puskesmas. The research informants are 1). Head of Puskesmas, 2). The Head of Section and Head of Administration. Visitors include patients who come for treatment and take care of health certificates. The research used descriptive qualitative research in order to explore in-depth information about the excellent service of Karang Rejo Health Centre. The results showed that first the Head of Puskesmas is a professional doctor, as a political actor has a very important role, especially when conducting vertical interactions and horizontal interactions. Vertical interaction with the leaders above him (head of department, regent) and horizontal interaction with the leaders below him (head of section & head of administration), causing Karang Rejo Health Centre to become independent with BLUD management. Secondly, in the dimensions of public service quality at Puskesmas Karang Rejo, West Tarakan Sub-district, Tarakan City, North Kalimantan Province, Indonesia, which has been running optimally with an achievement of 85% is the reliability dimension, the responsiveness dimension and the guarantee dimension. These dimensions can be optimal due to changes in the Puskesmas institution which was previously not independent in terms of its finances, turning into independent with BLUD management. Meanwhile, the dimensions of public service quality that have not run optimally and require improved management, amounting to 15%, namely the dimensions of physical evidence and empathy.